Comprehensive analysis of transcript start sites in ly49 genes reveals an unexpected relationship with gene function and a lack of upstream promoters. - Frances Gays; Alan S C Koh; Katarzyna M Mickiewicz; Jonathan G Aust; Colin G Brooks (PLoS ONE)
Comprehensive analysis of the transcription start sites of the Ly49 genes of C57BL/6 mice using the oligo-capping 5'-RACE technique revealed that the genes encoding the "missing self" inhibitory receptors, Ly49A, C, G, and I, were transcribed from multiple broad regions in exon 1, in the intron1/exon2 region, and upstream of exon -1b. Ly49E was also transcribed in this manner, and uniquely showed a transcriptional shift from exon1 to exon 2 when NK cells were activated in vitro with IL2. Remarkably, a large proportion of Ly49E transcripts was then initiated from downstream of the translational start codon. By contrast, the genes encoding Ly49B and Q in myeloid cells, the activating Ly49D and H receptors in NK cells, and Ly49F in activated T cells, were predominantly transcribed from a conserved site in a pyrimidine-rich region upstream of exon 1. An ∼200 bp fragment from upstream of the Ly49B start site displayed tissue-specific promoter activity in dendritic cell lines, but the corresponding upstream fragments from all other Ly49 genes lacked detectable tissue-specific promoter activity. In particular, none displayed any significant activity in a newly developed adult NK cell line that expressed multiple Ly49 receptors. Similarly, no promoter activity could be found in fragments upstream of intron1/exon2. Collectively, these findings reveal a previously unrecognized relationship between the pattern of transcription and the expression/function of Ly49 receptors, and indicate that transcription of the Ly49 genes expressed in lymphoid cells is achieved in a manner that does not require classical upstream promoters.